Differential Tick Salivary Protein Profiles and Human Immune Responses to Lone Star Ticks (Amblyomma americanum) From the Wild vs. a Laboratory Colony - Maldonado-Ruiz, L. Paulina; Montenegro-Cadena, Lidia; Blattner, Brittany; Menghwar, Sapna; Zurek, Ludek; Londono-Renteria, Berlin (Frontiers in Immunology, 2019)
Ticks are a growing concern to human and animal health worldwide and they are leading vectors of arthropod-borne pathogens in the United States. Ticks transmit a wide range of pathogenic microorganisms to humans and animals causing important health and economic impacts. Ticks are pool blood feeders that can attach to the host skin for days to weeks using their saliva to counteract the host defenses. Tick saliva, as in other hematophagous arthropods, contains pharmacological and immunological active compounds, which modulate local and systemic immune responses and induce antibody production. In the present study, we explore differences in the salivary gland extract (SGE) protein content of ticks, Amblyomma americanum, raised in a laboratory colony (CT) versus those found in the field (FT). Western-blot testing showed a set of different immunogenic bands for each antigen. Protein sequencing data from these bands revealed 39 proteins between 10 and 25 kDa from 19 CT and 20 FT. In addition, we measured human IgG antibodies against SGE from CT and FT in healthy individuals residing in Kansas. ELISA revealed that IgG antibody levels were higher when using the SGE from CT as compared to that from FT. Interestingly, antibody levels against both, LT and FT, were high in the warm months (May-June) and decreased in the cold months (September– November). In vitro testing using HUVEC, U937 and SHSY5Y human cell lines showed higher induction of expression of inflammatory related genes when treating cells with SGE from FT. In conclusion, our results show that the human serum samples reacted more with the CT protein content whereas the FT saliva induced a higher in vitro immune response, causing more inflammation. We hypothesize that differences in the salivary proteins between CT and FT may explain the differential immune responses observed in this study. It is possible that the salivary proteins absent in CT but present in FT are required for tick fitness in nature and possibly have helped to adapt to specific hosts.